Chemical constituents analysis of blue vitriol, brimstone and black stone using X-ray fluorescence technology and GC-MS: a quest for novel antifungals - Onyekachukwu Izuchukwu Udemezue; Onyekachi Ijeoma Udemezue; Evangeline Chinyere Udenweze; Chijioke Obinna Ezenwelu; Euphemia Afoma Ikegwuonu (Advances in Medical, Pharmaceutical and Dental Research, 2024)
New drugs especially antifungals are continually required by healthcare systems to address serious public health challenges such as resistance, toxicity, cost and scarcity. This research aimed at analyzing the chemical constituents of blue vitriol, brimstone and black stone using x-ray fluorescence technology and gas chromatography-mass spectroscopy (GC-MS); a quest for novel antifungal agents. The test isolates were obtained from high vaginal swab samples of patients attending a University Teaching Hospital in Anambra State, Nigeria. The isolates were identified based on their morphological, physiological and molecular characteristics. The minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) were determined using the broth dilution method. The inorganic and organic constituents of the natural compounds were determined using x-ray fluorescence technology and GC-MS respectively. The isolates include Candida albicans, C. tropicalis, C. glabrata and C. parapsilosis. The MIC and MFC of blue vitriol against the isolates ranges from 12.50mg/ml – 100mg/ml, brimstone (50mg/ml – 200mg/ml), black stone (200mg/ml) and ketoconazole(positive control):12.50mg/ml - 50mg/ml. The inorganic components found in blue vitriol include oxides of copper (43.7%), sulphur (29.4%), aluminium (1.2%); while the heavy metals arsenic, lead and nickel (all <0.009%). linoelaidic acid (24.92%) and oleic acid (12.97%) make up the organic components. Brimstone contains Oleic acid (10.26%), decanoic acid (28.37%), sulphur (94.72%), aluminum (3.46%), while Lead, arsenic and nickel all accounted for <0.0007%. Black stones comprise hexanoic acid (1.62%), oxides of iron (1.9%), sulphur (1.64%), potassium (2%), copper (0.2%), chlorine (0.98%); while nickel, lead and arsenic (all <0.002%). The study has revealed that blue vitriol, brimstone and black stones are good alternatives to conventional antifungal drugs.   Received: 28 May 2024 Accepted: 28 July 2024 Published: 20 September 2024